SHAROF RASHIDOV'S IMMORTAL PLACE IN THE LITERATURE AND HISTORY OF UZBEKISTAN ENTHUSIASTIC - Gʻayratova Gulzoda San'at daughter; Mukhtarov Sardorbek Saydullo son; Mamajonova Gulmira Davlat daughter (International Journal of Human Computing Studies, 2020)
Sharof Rashidov, a famous statesman, writer, who ruled the country in very difficult and difficult years, selflessly served for the development of our country, made a significant contribution to the development of our national literature and culture through his social and creative activities, is a great son of our people. , a clever and patriotic leader, a thoughtful and wise leader who led our mother Uzbekistan in very difficult and difficult years. He has been subjected to many trials and tribulations of life and destiny since childhood, and he has endured the hardships of life, both hot and cold. He was a child of a faithful and faithful nation that endured all the hardships of the Second World War. Under the tyranny of the dictatorship, in the most oppressive and threatening times, as a wise and hard-working leader of the country, he with his social and creative activity endured the hardships of that turbulent and murderous time, returned to his people, and at the same time a steadfast, kind and compassionate man who lived a life of respect for the dots, a well-known writer and teacher..